2016
DOI: 10.1134/s1990341316010016
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-flat galaxies selected from RFGC catalog. I. The sample properties

Abstract: We used the Revised Flat Galaxy Catalog (RFGC) to create a sample of ultra-flat galaxies (UFG) covering the whole northern and southern sky apart from the Milky Way zone. It contains 817 spiral galaxies seen edge-on, selected into the UFG sample according to their apparent axial ratios (a/b) B ≥ 10.0 and (a/b) R ≥ 8.53 in the blue and red bands, respectively. Within this basic sample we fixed an exemplary sample of 441 UFG galaxies having the radial velocities of V LG < 10000 km s −1 , Galactic latitude of | b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 20 publications
(25 reference statements)
1
40
0
Order By: Relevance
“…(1) the number of the galaxy in the RFGC catalog; (2) the equatorial coordinates; (3,4) the "blue" angular diameter in arcmin and apparent "blue" axial ratio from RFGC; (5) the heliocentric radial velocity of the galaxy in km s −1 ; (6) the effective wavelength of the filter (Å) in which the galaxy was exposed; (7) the exposure time in the Hα filter in sec; (8)…”
Section: Resultsmentioning
confidence: 99%
“…(1) the number of the galaxy in the RFGC catalog; (2) the equatorial coordinates; (3,4) the "blue" angular diameter in arcmin and apparent "blue" axial ratio from RFGC; (5) the heliocentric radial velocity of the galaxy in km s −1 ; (6) the effective wavelength of the filter (Å) in which the galaxy was exposed; (7) the exposure time in the Hα filter in sec; (8)…”
Section: Resultsmentioning
confidence: 99%
“…′ 0 is 70%, and the completeness of about 90% is achieved at the angular diameter of a blue = 1. ′ 2 [29]. We have strengthened the selection criteria to ensure the acceptable completeness (90%), reduce the selection effects, and at the same time to have a rather large number of galaxies remaining.…”
Section: Galaxiesmentioning
confidence: 99%
“…This sample covers the entire northern and southern sky, except for the region of the Milky Way (|b| < 10 • ) and has an approximately 90% completeness up to the angular diameter of a B = 1. ′ 2 [11]. From the analysis of this fairly representative sample, we concluded that about 60% of UF galaxies have not got any close neighbors within the projection distance of R p = 750 kpc and the radial velocity differences of | ∆V |< 500 km s −1 .…”
Section: Introductionmentioning
confidence: 80%